Analysis of optical modulators for radio over free space optical communication systems and radio over fiber systems - Prabu, K. (2014)
Radio over Free Space Optics (RoFSO) and Radio over Fiber (RoF) are recent technologies in optical communication systems. Both these technologies require some form of external optical modulator in the transmitter side. The commonly used optical modulators are Mach-Zehnder modulator (MZM) and Electro absorption modulator (EAM). In this paper, we analyze the performance of both Mach-Zehnder modulator and Electro absorption modulator for Radio over Free Space Optical Communication systems and it is compared with Radio over Fiber systems. We also discuss about the choice of optical modulator based on the intensity of output light signal.